1994
DOI: 10.1055/s-2007-994566
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Prediction of Fetal Pulmonary Hypoplasia in Pregnancies Complicated by Oligohydramnios and in Cases of Congenital Diaphragmatic Hernia: A Review

Abstract: The objective of this review is to discuss the current knowledge of fetal pulmonary hypoplasia and to summarize the clinical significance of the many ultrasound methods for predicting pulmonary hypoplasia in pregnancies complicated by oligohydramnios due to spontaneous rupture of the fetal membranes and in cases complicated by fetal congenital diaphragmatic hernia. We concluded that the presence or absence of polyhydramnios, fetal breathing movements, mediastinal shift, thoracic position of the stomach, fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Conventional 2D ultrasound has been used to evaluate fetal breathing movements, thoracic circumference, lung length and the ratio of thoracic circumference to abdominal circumference in order to predict lung volume. However, these parameters were not sufficiently sensitive or specific for clinical management in cases of pulmonary hypoplasia1–8. It has been shown that measuring lung volume with magnetic resonance imaging (MRI) has benefits over conventional 2D ultrasound38–45, particularly with the new high‐speed systems, which have clearer MR images with fewer motion artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional 2D ultrasound has been used to evaluate fetal breathing movements, thoracic circumference, lung length and the ratio of thoracic circumference to abdominal circumference in order to predict lung volume. However, these parameters were not sufficiently sensitive or specific for clinical management in cases of pulmonary hypoplasia1–8. It has been shown that measuring lung volume with magnetic resonance imaging (MRI) has benefits over conventional 2D ultrasound38–45, particularly with the new high‐speed systems, which have clearer MR images with fewer motion artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional two‐dimensional (2D) ultrasound, which is used routinely in obstetrics, has not proved sufficiently reliable to be used in the clinical diagnosis and management of pulmonary hypoplasia1–8. However, recent studies have indicated the value of three‐dimensional (3D) ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Such evidence may be obtained in fetuses exposed to oligohydramnios. As discussed below, some, but not all, reports indicate that such fetuses are more likely to develop lung hypoplasia if FBM are absent or reduced in incidence (Fox and Badalian 1994).…”
Section: Clinical Evidencementioning
confidence: 99%
“…do pulmão acometido131 , levando a condições de alta morbidade e mortalidade (50 -70%) no período neonatal 132. Uma vez que a hipoplasia pulmonar pode ser caracterizada pelo tamanho reduzido dos pulmões fetais, muitos estudos foram realizados com o intuito de se aferir o tamanho e o volume pulmonar90,132,[140][141][142][143] na tentativa de estimar a probabilidade do seu desenvolvimento[141][142][143][144] . Para esse fim, utilizou-se a pulmonar apenas nos casos de hérnia diafragmática congênita151,152 , embora isso não seja consenso na literatura.Raríssimos trabalhos descrevem a avaliação do volume pulmonar nos casos de derrame pleural pela ultrassonografia bidimensional.…”
unclassified